The Effect of Calcar Screw Use in Fractures of the Proximal Humerus (Journal of Academic Research, 2025)
Background:Proximal humerus fractures are common in elderly patients. Locking plates offer stable fixation, but loss of reduction and varus deformity still occur, especially with poor medial support.Methods:25 patients treated with PHILOS plates were studied. Calcar screws were used in some cases. Radiographs were assessed for neck-shaft angle and calcar screw position. Shoulder function was measured using the Oxford Shoulder Score.Results:91% of optimally placed calcar screws were associated with neck-shaft angles between 130°–150°. Malposition rate was 32%. Fixation failure occurred in 3 patients without calcar screws; none occurred in the calcar screw group.Conclusion:Use of calcar screws and achieving a neck-shaft angle between 130°–150° reduces fixation failure. Proper placement improves medial support and patient outcomes.
Keywords: Proximal humerus fracture; Calcar screw; Locking plate; Neck-shaft angle; Fixation failure